Bioecology of the Monkey (Rubus) Genus and Species Introduced to Uzbekistan (Texas Journal of Engineering and Technology, 2023)
The article is devoted to the topic “The family of monkeys brought to Uzbekistan, the bioecology of the species.” Introduces the genus of Rubus and the bioecology of the species